Tests for Normality in Linear Panel Data Models - Javier Alejo; Antonio Galvao; Gabriel Montes-Rojas; Walter Sosa-Escudero (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
A new Stata command, xtsktest, is proposed to explore non-normalities in linear panel data models. The tests explore skewness and excess kurtosis allowing researchers to identify departures away from gaussianity in both error components of a standard panel regression, sepa- rately or jointly. The tests are based on recent results by Galvao, Montes- Rojas, Sosa-Escudero and Wang (2013), and can be seen as extending the classical Bera-Jarque normality test for the case of panel data.
Keywords: J08; J24; J68; O15; 330; st0001; xtsktest; skewness; kurtosis; normality; panel data